Pengaruh Kinerja Lingkungan dan Kinerja Sosial Terhadap Kinerja Keuangan Dengan Firm Size Sebagai Moderasi - Trifani Isyahrahmaliza; Risal Risal; Aris Setiawan (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study analyzes the impact of environmental and social performance on the financial performance of energy companies listed on the Indonesian stock exchange between 2022 - 2024. Company size serves as a moderating variable. Environmental performance is measured using the PROPER rating, while social performance is measured through the disclosure of Corporate Social Responsibility (CSR) information. Financial performance is represented by the key performance indicators return on assets (ROA) and return on equity (ROE). The study employs a quantitative approach using panel data regression and moderated regression analysis (MRA). The sample comprises 61 energy companies with a total of 183 observations. The results show that environmental performance has no significant impact on ROA but a positive and significant impact on ROE. Conversely, social performance has a positive and significant impact on ROA but no significant impact on ROE. Both environmental and social performance significantly influence ROA and ROE. Furthermore, company size strengthens the link between environmental and social performance and financial performance. These findings suggest that larger companies have better capabilities in managing environmental and social activities, thereby increasing their financial performance and supporting the sustainability of their business operations.